ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA UNTUK BERKARIR MENJADI AKUNTAN PUBLIK - Nurkholis Fajri; Kirmizi Ritonga; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analyze of the influence of variable Job Intrinsic Value, Consideration of Labor Market, The Strenghts and Weaknesses of Public Accountant, Personality, and Professional Recognition to the interesting to get the career as public accountant. The samples in this study were students of existing state and private universities in Pekanbaru. Methods of data collection in this study is the method of questionnaires survey using instruments that are delivered diretcly to the students. Total respondents were are used in this analysis were 180 respondents. Methods of Analysis is conducted with a multiple regression analysis using SPSS (Statistical Product and Service Solutions) Version 17. The result of testing hypotheses using the t test, concluded H1, H2, H4, H5 is accepted which has a significance value p-value < 0,05, indicating that the variable job intrinsic value, consideration of labor market, personality, and professional recognition have influence to the interesting to get the career as public accountant. While variable the strenghts and weaknesses of public accountant have a significance value p-value > 0,05, H3 is not acceptable. The coefficient of determination in this study was 55,8 %. These four variables affect the dependent variable by 55,8 %, while 44,2 % is influenced by other variables that are not addressed in this study.Keywords : Intrinsic, Labor Consideration, Personality, Interesting as Public Accountant